Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2

Nanophase CulnS(2) nanosheets/CuS composite grown by the SILAR method leads to high performance as a counter electrode in dye sensitized solar cells - Bhosale, Reshma K.; Agarkar, Shruti A.; Agrawal, Ishita; Naphade, Rounak A.; Ogale, Satishchandra (RSC Advances, 2014)
Single phase CulnS(2) (CIS) nanosheets are synthesized on TiO2 coated FTO by the simple technique of Successive Ionic Layer Adsorption Reaction (SILAR) followed by annealing at 500 degrees C. Annealing at a lower temperature of 250 degrees C is found to yield CuS nanoparticles in addition to the CIS phase. Both single phase CIS and the CuS/CIS nanocomposite were examined as counter electrodes for a dye-sensitized solar cell (DSSC). The CIS-CuS composite is found to have a synergistic effect on the catalytic performance toward the reduction of tri-iodide, yielding a power conversion efficiency of 6.3% as compared to pristine CIS (5%) or CuS (3.5%). The possible reasons behind the high performance of the composite are elucidated using cyclic voltammetry (CV) measurements and electrochemical impedance spectroscopy (EIS).